Efficient sampling and data reduction techniques for probabilistic seismic lifeline risk assessment. - Jayaram, Nirmal
Probabilistic seismic risk assessment for spatially distributed lifelines is less straightforward than for individual structures. While procedures such as the 'PEER framework' have been developed for risk assessment of individual structures, these are not easily applicable to distributed lifeline systems, due to difficulties in describing ground motion intensity (e.g. spectral acceleration) over a region (in contrast to ground motion intensity at a single site, which is easily quantified using Probabilistic Seismic Hazard Analysis,) and since the link between the ground motion intensities and lifeline performance is usually not available in closed form. As a result, Monte Carlo simulation (MCS) and its variants are well suited for characterizing ground motions and computing resulting losses to lifelines. This paper proposes a simulation based framework for developing a small but stoichastically representative catalog of earthquake ground motion intensity maps that can be used for lifeline risk assessment. In this framework, Importance Samping is used to preferentially sample 'important' ground motion intensity maps and K-Means Clustering is used to identify and combine redundant maps in order to obtain a small catalog. The effects of sampling and clustering are accounted for through a weighting on each remaining map, so that the resulting catalog is still a probabilistically correct representation. The feasibility of the proposed simulation framework is illustrated by using it to assess the seismic risk of a simplified model of the San Francisco Bay Area transportation network. A catalog of just 150 intensity maps is generated to represent hazard at 1038 sties from 10 regional fault segments causing earthquakes with magnitudes between five and eight. The risk estimates obtained using these maps are consistent with those obtained using conventional MCS utilizing many orders to drastically reduce the computational expense of a simulation-based risk assessment, without compromising the accuracy of the risk estimates. This will facilitate computationally intensive risk analysis of systems such as transportation networks. Finally, the study shows computationally intensive risk analysis of systems such as transportation networks. Finally, the study shows that the uncertainties in the ground motion intensities and the spatial correlations between ground motion intensities at various sites must be modeled in order to obtain unbiased estimates of lifeline risk.
Keywords: Lifeline; Seismic risk; Efficient simulation; Importance sampling; k-means clustering; Transportation network